ANALISIS TINDAKAN DISKRIMINASI PESERTA DIDIK DI SEKOLAH DASAR: STUDI KUALITATIF MENGENAI FAKTOR PEMICU DAN DAMPAK NYA PADA PESERTA DIDIK FASE C KELAS VI - Yohana R Tagu Pati; Yuliana G E Kolin; Narwis Friando Makasar; Merlin E Selan; Jimylton Dethan (STKIP Subang, 2025)
Discrimination is an unfair action such as limiting, differentiating, and excluding directly or indirectly on the basis of religion, race, ethnicity, group, language, skin color, gender, social status, or economic status. The purpose of this study is to determine the causes and impacts experienced by victims of discrimination at SDN Kelapa Lima. This study uses a qualitative method. Based on interview data, the factors causing discrimination at SDN Kelapa Lima are bullying behavior. Where students often get teased using their parents' names, older siblings' names and are also teased because they have a different physical appearance from others such as weight, height (electricity pole), curly hair, skin color, parents' jobs and knowledge abilities (IQ) as well as differentiating treatment such as being rejected or not accepted in the circle of friends. The conclusion: discrimination is an unpleasant act that mocks the physical appearance of peers by calling them electric poles, calling friends by their parents' names and older siblings' names and treatment such as being rejected or not accepted in the circle of friends.